A inversão das distâncias - Do Som do Corpo ao Corpo do Som - Menezes, Flo [UNESP] (My University, 2014)
This essay deals with the relationship between the body of the composer and his sounds, approaching - by a philosophical point of view - the process of objectivation of sound along the history of musical writing (escritura = musical scripture), until coming up the emergence of electroacoustic music. At this point, the text handles with the dialectic between analogical and digital resources and with the most crucial problems of electroacoustic music in our days.
The inversion of the distances - From the sound of the body to the body of sound
Keywords: Electroacoustic poetics; Musical composition; Philosophy of music